2021
DOI: 10.4314/evj.v25i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of breed on the quality of in vivo produced embryos from Boran and Holstein Friesian cross dairy breed in Ethiopia

Abstract: The variation of the dairy breed can determine the success of bovine embryo transfer by influencing the quantity and quality of in vivo embryo production. In this experiment, output and quality of in vivo produced embryos using semen of progeny tested Holstein Friesian (HF) sire in Boran and HF*Boran F1 cross cows, and semen from purebred Boran sire in HF*Boran F1 cross and Boran cows were evaluated. Boran (n=18) and HF*Boran cross (n=18) breed donor dams were superovulated using a previously optimized follicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These groups of medications have a better quality of data and are hence preferred as opposed to other systemic immunotherapies like Azathioprine, methotrexate, and Mycophenolate Mofetil where the evidence is based on observational studies (15,16,17). Yet, multiple observational studies and local data suggest that these agents can be e caciously employed to treat NMOSD, leading to favorable clinical outcomes (18,19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These groups of medications have a better quality of data and are hence preferred as opposed to other systemic immunotherapies like Azathioprine, methotrexate, and Mycophenolate Mofetil where the evidence is based on observational studies (15,16,17). Yet, multiple observational studies and local data suggest that these agents can be e caciously employed to treat NMOSD, leading to favorable clinical outcomes (18,19,20).…”
mentioning
confidence: 99%
“…Based on our experience of treating this patient and local data from other documented cases, it is suggested that patients can be effectively treated with available therapies, leading to positive clinical and functional outcomes, unless newer immunosuppressive treatments targeting the underlying pathophysiology are available (19,20,21,22,23,24).…”
mentioning
confidence: 99%